Model Permainan Kassep Untuk PJOK di Sekolah Dasar Paguyaman: Studi Pustaka - Yusuf Wungguli; Aisah R Pomatahu; Mirdayan Pauweni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to examine the potential for developing the Kassep game model in the context of PJOK learning in elementary schools, especially in the District. The Kassep game model was developed from rounders and soccer for use in Physical Education, Sports, and Health (PJOK) lessons in elementary schools in the Paguyaman District. Through a literature review, this article examines various studies related to basic throwing and catching techniques, the development of small ball game models, and the application of traditional rounders and soccer games as learning media. The results of the study show that the integration of rounders and soccer elements in the Kassep model can improve basic motor skills, especially throwing and catching techniques, and increase student motivation to learn. This model is expected to be an innovative alternative in PJOK learning in elementary schools to improve the effectiveness and excitement of small ball game learning. Keywords: game model, baseball, soccer, physical education, elementary school